FORMULATION OF NANOSUSPENSION COMBINATION BASIL LEAF EXTRACT AND CILEMBU SWEET POTATO SACCHARIDE AND ITS OXIDATIVE STRESS INHIBITING EFFECT IN VITRO - Nurrizqia Kahan, Alfitri
Basil (Ocimum americanum L.) is one of the plants known as a natural antioxidant because it contains phenolic compounds. In addition, saccharides from cilembu sweet potatoes (Ipomoea batatas L.) also have antioxidant activity and have been modified through phosphorylation to enhance their water solubility. This study aimed to develop a nanosuspension system containing basil leaf extract and saccharide extract from sweet potatoes and to observe the effect on reducing oxidative stress. The two extracts were combined using a high-pressure homogenization method, resulting in a nanosuspension formulation. Variations in the concentration of basil leaf extract, saccharide cilembu sweet potato, and arginine were made. The nanosuspension method was optimized with ultraturrax and probe sonication. Subsequently, lyophilization was performed to provide long-term stability. Then the nanosuspension was characterized. Additionally, cell viability and the inhibitory effects on reactive oxygen species (ROS) and nitric oxide (NO) in RAW 264.7 cells induced by H2O2 and lipopolysaccharide (LPS) were evaluated. The optimization results showed that the formula with 1% basil leaf extract, 5% saccharide cilembu sweet potato, and 0.5% arginine using an ultraturrax method at 10000 rpm for 5 min, followed by probe sonication at 60% amplitude with a 45:15 pulse for 5 min, produced a particle size of 222.10 ± 29.86 nm, antioxidant activity of 266.8 ± 0.42 mg AEAC/g, the highest RAW 264.7 cell viability at a concentration of 50 µg/mL. The inhibitory effects on ROS and NO stimulated by H2O2 and LPS showed the highest values at a concentration of 75 µg/mL. These results indicated that the nanosuspension had the potential to enhance antioxidant activity and inhibit oxidative stress.